G protein-coupled receptor kinase 5 (GRK5) contributes to impaired cardiac function and immune cell recruitment in post-ischemic heart failure. Issue 1 (9th February 2021) - de Lucia, Claudio; Grisanti, Laurel A; Borghetti, Giulia; Piedepalumbo, Michela; Ibetti, Jessica; Lucchese, Anna Maria; Barr, Eric W; Roy, Rajika; Okyere, Ama Dedo; Murphy, Haley Christine; Gao, Erhe; Rengo, Giuseppe; et al.
Abstract: Aims : Myocardial infarction (MI) is the most common cause of heart failure (HF) worldwide. G protein-coupled receptor kinase 5 (GRK5) is upregulated in failing human myocardium and promotes maladaptive cardiac hypertrophy in animal models. However, the role of GRK5 in ischemic heart disease is still unknown. In this study, we evaluated whether myocardial GRK5 plays a critical role post-MI in mice and included the examination of specific cardiac immune and inflammatory responses. Methods and results : Cardiomyocyte-specific GRK5 overexpressing transgenic mice (TgGRK5) and non-transgenic littermate control (NLC) mice as well as cardiomyocyte-specific GRK5 knockout mice (GRK5cKO) and wild type (WT) were subjected to MI and, functional as well as structural changes together with outcomes were studied. TgGRK5 post-MI mice showed decreased cardiac function, augmented left ventricular dimension and decreased survival rate compared to NLC post-MI mice. Cardiac hypertrophy and fibrosis as well as fetal gene expression were increased post-MI in TgGRK5 compared to NLC mice. In TgGRK5 mice, GRK5 elevation produced immuno-regulators that contributed to the elevated and long-lasting leukocyte recruitment into the injured heart and ultimately to chronic cardiac inflammation. We found an increased presence of pro-inflammatory neutrophils and macrophages as well as neutrophils, macrophages and T-lymphocytes at 4-days and 8-weeks respectively post-MI in TgGRK5 hearts. Conversely, GRK5cKO mice were protected from ischemic injury and showed reduced early immune cell recruitment (predominantly monocytes) to the heart, improved contractility and reduced mortality compared to WT post-MI mice. Interestingly, cardiomyocyte-specific GRK2 transgenic mice did not share the same phenotype of TgGRK5 mice and did not have increased cardiac leukocyte migration and cytokine or chemokine production post-MI. Conclusions : Our study shows that myocyte GRK5 has a crucial and GRK-selective role on the regulation of leucocyte infiltration into the heart, cardiac function and survival in a murine model of post-ischemic HF, supporting GRK5 inhibition as a therapeutic target for HF. Graphical Abstract: